Status quo of chemical weed control in rice in sub-Saharan Africa - Rodenburg, J.; Johnson, J.M.; Dieng, I.; Senthilkumar, Kalimuthu; Vandamme, Elke; Akakpo, C.; Allarangaye, M.D.; Baggie, I.; Bakare, S.O.; Bam, R.K.; Bassoro, I.; Abera, B.B.; et al. (Springer, 2019)
If future rice production is to contribute to food security for the increasing population of sub-Saharan Africa (SSA), effective strategies are needed to control weeds, the crop’s fiercest competitors for resources. To gain better insights into farmers’ access to, and use of, herbicides as part of weed control strategies, surveys were conducted in key rice production locations across SSA. Farm surveys were held among 1965 farmers across 20 countries to collect data on rice yields, farmer’s weed management practices, herbicide use, frequencies of interventions and information sources regarding herbicides. Markets were surveyed across 17 countries to collect data on herbicide availability, brand names and local prices (converted to US$ ha−1). Herbicides are used by 34% of the rice farmers in SSA, but adoption ranges from 0 to 72% across countries. Herbicides are more often used by men (40%) than by women (27%) and more often in irrigated (44% of farmers) than in rainfed lowland (36%) or upland rice growing environments (24%). Herbicides are always used supplementary to hand weeding. Following this combination, yield loss reductions in irrigated lowlands and rainfed uplands are estimated to be 0.4 t ha−1 higher than hand weeding alone. In rainfed lowlands no benefits were observed from herbicide use. Sixty-two percent of the herbicides sold at rural agro-chemical supply markets are unauthorized. These markets are dominated by glyphosate and 2,4-D, sold under 55 and 41 different brand names, respectively, and at relatively competitive prices (below average herbicide price of US $17 ha−1). They are also the most popular herbicides among farmers. For advice on herbicide application methods, farmers primarily rely on their peers, and only a few receive advice from extension services (<23%) or inform themselves by reading the product label (<16%). Herbicide application timings are therefore often (38%) sub-optimal. Herbicide technologies can contribute to reduced production losses in rice in SSA. However, through negative effects on crop, environment and human health, incorrect herbicide use may unintentionally counteract efforts to increase food security. Moving away from this status quo will require strict implementation and monitoring of national pesticide regulations and investment in research and development to innovate and diversify the currently followed weed management strategies, agricultural service provision and communications with farmers.